Analysing trends of psychiatric disorders, treatment and service use across time in adults with borderline intellectual impairment: A cross-sectional study of private households. (July 2022) - Lim, Amanda; Totsika, Vaso; Ali, Afia
Abstract: While there is evidence that mental health problems are more prevalent in people with borderline intellectual functioning (BIF) compared to the general population, it is not known to what extent this has varied or changed over time and whether there have been changes in access to services. This paper compares the prevalence rates of psychiatric disorders and monitors trends in treatment and services in this population compared to the general population. We conducted secondary analysis on the Adult Psychiatric Morbidity Surveys carried out in England in 2000, 2007 and 2014. The total sample analysed included 21, 796 participants, with 12.8% of individuals identified with BIF (n = 2786). Regression models were used to examine trends in psychiatric disorders, treatment and service use across the three datasets. People with BIF had significantly higher odds of developing mood and anxiety disorders, psychosis, drug dependence and suicidal behaviour than the general population, increasing at each subsequent timepoint. They received significantly more pharmacological treatments than the general population but have had increasingly more access to general practitioners, community care and daycare services over time. This study shows increasing prevalence rates of several mental disorders in people with BIF. Access to day-care, community care and healthcare services has increased over time for this group but not formal psychiatric care. These changes over time underline some of the problems this population faces, emphasizing a need to recognize that this is a population often overlooked in research and clinical practice.